How to improve the corporate framework of the Portuguese cork industry - Ramos, Luís Almeida (2022)
With the rising concern towards ecological problems, society is changing and starting to give more value on environmentally friendly initiatives. Consequently, the Linear Economy model is beginning to diminish, providing to Circular Economy (CE) an opportunity to emerge. Although by nature a "green" industry, the Portuguese cork does not fully utilize the CE model. Thus, the purpose of this investigation is to understand if the Portuguese cork industry has the capacity implement a CE paradigm and how it could benefit the industry, by studying the possibility of incorporating a closed loop supply chain, the capability to use technologies from the fourth industrial revolution (4IR), the sustainability policies of this industry and its ability to innovate and develop new products. To achieve a conclusion, it was analysed various findings and conducted seven interviews to people related to the Portuguese cork industry, that helped answer the Research Questions due to their feedback on several matters related to the implementation of a CE paradigm in this industry. The results determine that, in theory, the Portuguese cork industry would benefit from a CE paradigm. The industry’s policies are sustainable and it is capable to innovate and develop new products. However, the implementation would not be easy because the majority of business keep focusing on cork stoppers, there is a lack of fundings to obtain 4IR technologies and it is difficult for the industry to close the loop of the supply chain, especially to its main product, the cork stoppers.